Employing a visualized searching system to assist elementary students' tactics and success of storybook searching. Issue 3 (12th June 2017) - Chao, Po-Yao; Lin, Chia-Ching; Wu, Ming-Shiang
Abstract : Purpose: The purpose of this paper is twofold: first, to develop a visualized search system utilizing graphical images to represent the story elements and concepts to help elementary students describe and seek their desired storybooks; and second, to explore the effect of the proposed visualized search system on elementary students' tactics, success, and motivation for seeking storybooks. Design/methodology/approach: A quasi-experimental approach was conducted with a sample of 61 elementary students in this study. The students' tactics, motivation and the success of their storybook searching were addressed as dependent variables for further comparisons of the visualized searching system and a conventional keyword searching system. Findings: The results revealed that the students in the experimental group exhibited more frequent tactics and greater motivation for storybook searching than those in the control group. Further χ 2 analysis indicated a significant relationship between the searching interface and the success of the students' storybook searching. Originality/value: This paper proposes a new visual search approach which allows young children to search for storybooks by describing an intended storybook in terms of its characters, objects, or the background colors of the cover page. The findings provide some evidence of the effectiveness of the visualized searching interface in terms of promoting young children's learning through storybook searching and reading activities.